Reaction Mechanism of Human PAICS Elucidated by Quantum Chemical Calculations - Prejanò, Mario; Škerlová, Jana; Stenmark, Pål; Himo, Fahmi (Journal of the American Chemical Society, 2022)
Human PAICS is a bifunctional enzyme that is involved in the de novo purine biosynthesis, catalyzing the conversion of aminoimidazole ribonucleotide (AIR) into N-succinylcarboxamide-5-aminoimidazole ribonucleotide (SAICAR). It comprises two distinct active sites, AIR carboxylase (AIRc) where the AIR is initially converted to carboxyaminoimidazole ribonucleotide (CAIR) by reaction with CO2 and SAICAR synthetase (SAICARs) in which CAIR then reacts with an aspartate to form SAICAR, in an ATP-dependent reaction. Human PAICS is a promising target for the treatment of various types of cancer, and it is therefore of high interest to develop a detailed understanding of its reaction mechanism. In the present work, density functional theory calculations are employed to investigate the PAICS reaction mechanism. Starting from the available crystal structures, two large models of the AIRc and SAICARs active sites are built and different mechanistic proposals for the carboxylation and phosphorylation-condensation mechanisms are examined. For the carboxylation reaction, it is demonstrated that it takes place in a two-step mechanism, involving a C-C bond formation followed by a deprotonation of the formed tetrahedral intermediate (known as isoCAIR) assisted by an active site histidine residue. For the phosphorylation-condensation reaction, it is shown that the phosphorylation of CAIR takes place before the condensation reaction with the aspartate. It is further demonstrated that the three active site magnesium ions are involved in binding the substrates and stabilizing the transition states and intermediates of the reaction. The calculated barriers are in good agreement with available experimental data.
Keywords: Humans; Ribonucleotides; ribonukleotidy; lidé; Catalytic Domain; kyselina asparagová; Aspartic Acid; katalytická doména